Low-temperature electrolyte and preparation method and application thereof
By using a low-temperature electrolyte with a ratio of magnesium salt to sodium salt in sodium salt (2.5~3.0):0.5 in sodium ion batteries, the hydrogen bond network was broken, and the problem of poor performance of sodium ion batteries at low temperatures was solved, and high ionic conductance was achieved rate and good cycle performance.
Patent Information
- Application Number
- CN202411342343.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The poor operating performance of sodium ion batteries in low temperature environments leads to a decrease in ion conductivity, a decrease in capacity retention, and even the electrolyte coagulation and fails to work normally.
Provide a low-temperature electrolyte containing the molar ratio of magnesium salt and sodium salt is (2.5-3.0): 0.5. Through Mg2+ in the magnesium salt as a hydrogen bond acceptor, the hydrogen bond network between water molecules is broken and the electrolyte is reduced. freezing point and viscosity to improve ionic conductivity.
The high ionic conductivity and good cycling performance of the electrolyte at low temperatures are achieved, ensuring that the sodium ion battery has good capacity retention and excellent cycling performance under low temperature conditions.
Smart Images

Figure CN119208767A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a low-temperature electrolyte and a preparation method and application thereof. Background Art
[0002] In recent years, sodium-ion batteries have attracted much attention due to their similar working principles and multiple advantages to lithium-ion batteries. Compared with lithium-ion batteries, the main advantage of sodium-ion batteries is their low cost. Due to the abundant reserves and wide distribution of sodium, the cost of sodium salts is much lower than that of lithium salts, about one twenty-fifth of that of lithium salts. And because the physical and chemical properties of sodium are similar to those of lithium, sodium-ion batteries are more competitive in large-scale power station energy storage systems that need to pay attention to cost-effectiveness and safety. Therefore, in some application scenarios, sodium-ion batteries may become a more suitable choice. Compared with traditional lead-acid batteries, zinc-manganese batteries and nickel-cadmium batteries, sodium-ion batteries have significant advantages in cycle life, energy density cost, energy saving and environmental protection. However, sodium-ion batteries do not perform well in low-temperature environments. This is because the diffusion rate of sodium ions is low at low temperatures, the migration speed of sodium ions slows down, resulting in a decrease in the ionic conductivity of the electrolyte, a decrease in the capacity retention rate of the battery at low temperatures, and even causes the electrolyte to solidify, causing the battery to fail directly and unable to work normally. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a low-temperature electrolyte and a preparation method and application thereof. The low-temperature electrolyte provided by the present invention has an extremely low freezing point (-50°C) and excellent ionic conductivity at low temperatures. The sodium ion battery prepared therefrom has good capacity retention and excellent cycle performance.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The invention provides a low-temperature electrolyte, comprising a magnesium salt, a sodium salt and water; the molar ratio of the magnesium salt to the sodium salt is (2.5-3.0):0.5.
[0006] Preferably, the magnesium salt includes one or more of magnesium chloride, magnesium perchlorate and magnesium nitrate; the magnesium chloride is anhydrous magnesium chloride and / or magnesium chloride hexahydrate.
[0007] Preferably, the sodium salt includes one or more of sodium chloride, sodium hexafluorophosphate, sodium nitrate, sodium perchlorate and sodium trifluoromethanesulfonate.
[0008] Preferably, the ratio of the amount of the magnesium salt to the volume of water is (2.5-3.0) mol:1L.
[0009] The present invention also provides a method for preparing the low-temperature electrolyte described in the above technical solution, comprising the following steps:
[0010] The magnesium salt, the sodium salt and water are mixed to obtain the low-temperature electrolyte.
[0011] Preferably, the mixing is carried out under stirring conditions, and the stirring speed is 300-400 r / min.
[0012] The present invention also provides the use of the low-temperature electrolyte described in the above technical solution or the low-temperature electrolyte prepared by the preparation method described in the above technical solution in a sodium ion battery.
[0013] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte, wherein the electrolyte is the low-temperature electrolyte described in the above technical solution or the low-temperature electrolyte prepared by the preparation method described in the above technical solution.
[0014] Preferably, the method for preparing the positive electrode sheet comprises the following steps:
[0015] Na2CoFe(CN)6, a conductive agent and a binder are mixed and ground, and the obtained mixture is mixed with an organic solvent to obtain a positive electrode slurry;
[0016] The positive electrode slurry is coated on a substrate and then dried to obtain the positive electrode sheet.
[0017] Preferably, the method for preparing the negative electrode sheet comprises the following steps:
[0018] The activated carbon, the conductive agent and the binder are mixed and ground, and the obtained mixture is mixed with an organic solvent to obtain a negative electrode slurry;
[0019] The negative electrode slurry is coated on a substrate and then dried to obtain the negative electrode sheet.
[0020] The present invention provides a low-temperature electrolyte, comprising magnesium salt, sodium salt and water; the molar ratio of the magnesium salt to the sodium salt is (2.5-3.0):0.5. 2+ It can act as a hydrogen bond acceptor, combining with hydrogen bonds in water, breaking the hydrogen bond network between water molecules, thereby significantly reducing the freezing point of the electrolyte, reducing the viscosity of the electrolyte, and improving the ionic conductivity of the electrolyte at low temperatures. The sodium ion battery prepared with it has good capacity retention and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Optical photographs of the low-temperature electrolyte prepared in Example 1 and the electrolytes prepared in Comparative Examples 1 to 6 at different temperatures;
[0022] Figure 2A Raman spectrum comparison diagram of the low-temperature electrolyte prepared in Example 1, the electrolytes prepared in Comparative Examples 1 and 4, and deionized water;
[0023] Figure 3 A diagram of a sodium ion battery prepared in Application Example 1;
[0024] Figure 4 This is a graph showing the low temperature cycle performance of the sodium ion battery prepared in Application Example 1 at a current density of 10C;
[0025] Figure 5 A conductivity comparison diagram of the low-temperature electrolyte prepared in Example 1 and the aqueous sodium ion battery electrolyte prepared in Comparative Example 7;
[0026] Figure 6 This is a comparison chart of the actual application scenarios of the sodium-ion battery prepared in Application Example 1 and commercial batteries. DETAILED DESCRIPTION
[0027] The invention provides a low-temperature electrolyte, comprising a magnesium salt, a sodium salt and water; the molar ratio of the magnesium salt to the sodium salt is (2.5-3.0):0.5.
[0028] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0029] As an embodiment, the magnesium salt includes one or more of magnesium chloride, magnesium perchlorate and magnesium nitrate; the magnesium chloride is anhydrous magnesium chloride and / or magnesium chloride hexahydrate, and in a specific embodiment, it is magnesium chloride hexahydrate.
[0030] As an embodiment, the sodium salt includes one or more of sodium chloride, sodium hexafluorophosphate, sodium nitrate, sodium perchlorate and sodium trifluoromethanesulfonate, and in a specific embodiment, it is sodium chloride; the water is deionized water.
[0031] In a specific embodiment, the molar ratio of the magnesium salt to the sodium salt is 2.8:0.5.
[0032] As an embodiment, the ratio of the amount of the magnesium salt to the volume of water is (2.5-3.0) mol:1L, and in a specific embodiment it is 2.8 mol:1L.
[0033] Mg in the low-temperature electrolyte provided by the present invention 2+ It can act as a hydrogen bond acceptor, combining with hydrogen bonds in water, breaking the hydrogen bond network between water molecules, thereby significantly reducing the freezing point of the electrolyte, reducing the viscosity of the electrolyte, and improving the ionic conductivity of the electrolyte at low temperatures. The sodium ion battery prepared with it has good capacity retention and excellent cycle performance.
[0034] The present invention also provides a method for preparing the low-temperature electrolyte described in the above technical solution, comprising the following steps:
[0035] The magnesium salt, the sodium salt and water are mixed to obtain the low-temperature electrolyte.
[0036] As an implementation mode, the mixing is carried out under stirring conditions, the stirring speed is 300-400 r / min, and the time is 12 hours; the equipment used for the stirring is a magnetic stirrer.
[0037] In a specific embodiment, the stirring speed is 300 r / min and the time is 12 h.
[0038] As an embodiment, after the mixing, the present invention further comprises: allowing the mixed solution to stand to obtain the low-temperature electrolyte, and the standing time is 12 hours.
[0039] When dissolving salt, air will be introduced into the solution to form bubbles. The present invention allows the air to escape by standing still, thereby preventing these bubbles from affecting the performance of the low-temperature electrolyte.
[0040] The present invention also provides the use of the low-temperature electrolyte described in the above technical solution or the low-temperature electrolyte prepared by the preparation method described in the above technical solution in a sodium ion battery.
[0041] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte, wherein the electrolyte is the low-temperature electrolyte described in the above technical solution or the low-temperature electrolyte prepared by the preparation method described in the above technical solution.
[0042] As an embodiment, the diaphragm is a Whatman diaphragm.
[0043] As an embodiment, the method for preparing the positive electrode sheet comprises the following steps:
[0044] Na2CoFe(CN)6, a conductive agent and a binder are mixed and ground, and the obtained mixture is mixed with an organic solvent to obtain a positive electrode slurry;
[0045] The positive electrode slurry is coated on a substrate and then dried to obtain the positive electrode sheet.
[0046] As an embodiment, the preparation method of Na2CoFe(CN)6 comprises the following steps:
[0047] Completely dissolving sodium ferrocyanide and sodium chloride in deionized water to obtain solution A;
[0048] Completely dissolving cobalt chloride hexahydrate and trisodium citrate dehydrate in deionized water to obtain solution B;
[0049] Under the condition of the first stirring, the solution B is added dropwise to the solution A, and then a second stirring is performed. The solid obtained by solid-liquid separation is washed and dried in sequence to obtain Na2CoFe(CN)6 (cobalt-based Prussian blue material).
[0050] As an embodiment, the dosage ratio of sodium ferrocyanide, sodium chloride and deionized water is 2mmol:7g:100mL; the dosage ratio of cobalt chloride hexahydrate, trisodium citrate dehydrate and deionized water is 2mmol:7mmol:100mL; the dropwise addition is carried out with a peristaltic pump; the dropwise addition rate is 2mL / min; the first stirring speed is 300r / min; the second stirring speed is 300r / min; the second stirring temperature is 60°C; the second stirring time is 24h; the solid-liquid separation is preferably filtration; the reagent used for washing is deionized water; the number of washings is 3 to 5 times; the washing is washing with deionized water and then centrifuging; the centrifugal speed is 9000r / min; the centrifugal time is 20min; the drying is freeze-drying; the freeze-drying temperature is -50°C; the freeze-drying time is 48h.
[0051] As an embodiment, the conductive agent is acetylene black; the binder is polyvinylidene fluoride; the organic solvent is N-methyl-2-pyrrolidone; the mass ratio of Na2CoFe(CN)6, the conductive agent and the binder is 7:2:1; the mass ratio of the binder and the organic solvent is 1:19.
[0052] The present invention has no particular limitation on the grinding method, and any grinding method known in the art may be used.
[0053] As an embodiment, the substrate is carbon paper; the coating device is a four-sided film coater; the coating amount of the positive electrode slurry coated on the substrate is 1 to 1.5 mg / cm 2 ; The equipment used for the drying is a vacuum oven; the drying temperature is 70-90°C and the drying time is 10-12h.
[0054] As an embodiment, the method for preparing the negative electrode sheet comprises the following steps:
[0055] The activated carbon, the conductive agent and the binder are mixed and ground, and the obtained mixture is mixed with an organic solvent to obtain a negative electrode slurry;
[0056] The negative electrode slurry is coated on a substrate and then dried to obtain the negative electrode sheet.
[0057] As an implementation mode, the conductive agent is acetylene black; the binder is polyvinylidene fluoride; the organic solvent is N-methyl-2-pyrrolidone; the mass ratio of the activated carbon, the conductive agent and the binder is 8:1:1; the mass ratio of the binder and the organic solvent is 1:19.
[0058] The present invention has no particular limitation on the grinding method, and any grinding method known in the art may be used.
[0059] As an embodiment, the substrate is carbon paper; the coating device is a four-sided film coater; the coating amount of the negative electrode slurry coated on the substrate is 1 to 1.5 mg / cm 2 ; The equipment used for the drying is a vacuum oven; the drying temperature is 70-90°C and the drying time is 10-12h.
[0060] As an embodiment, the preparation method of the sodium ion battery is: assembling a negative electrode sheet, a separator, and a positive electrode sheet in order, dripping the low-temperature electrolyte on the separator, and standing to obtain the sodium ion battery. As an embodiment, the standing time is 12 hours.
[0061] As an embodiment, the sodium ion battery further includes: a tab is arranged on the outer side of the positive electrode sheet and the negative electrode sheet; and the tab is a titanium foil.
[0062] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0063] Example 1
[0064] MgCl2·6H2O and NaCl were added into deionized water, stirred at 300 r / min for 12 h, and allowed to stand for 12 h to obtain a low-temperature electrolyte;
[0065] The molar ratio of MgCl2·6H2O to NaCl is 2.8:0.5;
[0066] The ratio of the amount of MgCl2·6H2O to the volume of deionized water is 2.8 mol:1L.
[0067] Comparative Example 1
[0068] The difference from Example 1 is that only NaCl is added to the deionized water without adding MgCl2·6H2O, and the ratio of the amount of NaCl to the volume of deionized water is 0.5 mol:1L.
[0069] Comparative Example 2
[0070] The difference from Example 1 is that the molar ratio of MgCl2·6H2O and NaCl is 0.5:0.5, the ratio of the amount of MgCl2·6H2O to the volume of deionized water is 0.5 mol:1 L, and the remaining operations are the same as those in Example 1.
[0071] Comparative Example 3
[0072] The difference from Example 1 is that the molar ratio of MgCl2·6H2O to NaCl is 1.0:0.5, the ratio of the amount of MgCl2·6H2O to the volume of deionized water is 1.0 mol:1 L, and the remaining operations are the same as those in Example 1.
[0073] Comparative Example 4
[0074] The difference from Example 1 is that the molar ratio of MgCl2·6H2O to NaCl is 1.5:0.5, the ratio of the amount of MgCl2·6H2O to the volume of deionized water is 1.5 mol:1 L, and the remaining operations are the same as those in Example 1.
[0075] Comparative Example 5
[0076] The difference from Example 1 is that the molar ratio of MgCl2·6H2O to NaCl is 2.0:0.5, the ratio of the amount of MgCl2·6H2O to the volume of deionized water is 2.0 mol:1 L, and the other operations are the same as those in Example 1.
[0077] Comparative Example 6
[0078] The difference from Example 1 is that the molar ratio of MgCl2·6H2O to NaCl is 3.5:0.5, the ratio of the amount of MgCl2·6H2O to the volume of deionized water is 3.5 mol:1 L, and the other operations are the same as those in Example 1.
[0079] Comparative Example 7
[0080] Aqueous sodium ion battery electrolyte (1mol / LNa2SO4).
[0081] Application Example 1
[0082] Completely dissolve 2 mmol of sodium ferrocyanide and 7 g of sodium chloride in 100 mL of deionized water to obtain solution A;
[0083] 2 mmol of cobalt chloride hexahydrate and 7 mmol of trisodium citrate dehydrate were completely dissolved in 100 mL of deionized water to obtain solution B;
[0084] Under the stirring condition of 300 r / min, the solution B was added dropwise to the solution A at a rate of 2 mL / min using a peristaltic pump, and then the mixed solution was stirred at 300 r / min at 60° C. for 24 h, and the solid obtained by solid-liquid separation (filtration) was washed 3 times with deionized water, and after each washing, it was centrifuged at 9000 r / min for 20 min, and finally freeze-dried at -50° C. for 48 h to obtain Na2CoFe(CN)6;
[0085] The Na2CoFe(CN)6, polyvinylidene fluoride and conductive agent acetylene black were mixed and ground in a mass ratio of 7:2:1, and then N-methyl-2-pyrrolidone was added dropwise, and the mass ratio of polyvinylidene fluoride to N-methyl-2-pyrrolidone was 1:19 to obtain a positive electrode slurry; the positive electrode slurry was coated on carbon paper using a four-sided coater, and the coating amount was 1 mg / cm 2 , and then transferred to a vacuum oven and dried at 70°C for 12 hours to obtain a positive electrode sheet;
[0086] Activated carbon, polyvinylidene fluoride and conductive agent acetylene black were mixed and ground in a mass ratio of 8:1:1, and N-methyl-2-pyrrolidone was added dropwise, and the mass ratio of polyvinylidene fluoride to N-methyl-2-pyrrolidone was 1:19 to obtain a negative electrode slurry; the negative electrode slurry was coated on carbon paper using a four-sided coater, and the coating amount was 1 mg / cm 2 , and then transferred to a vacuum oven and dried at 70°C for 12 hours to obtain a negative electrode sheet;
[0087] Titanium foil was used as the tab, and the tab, negative electrode sheet, Whatman diaphragm, positive electrode sheet, and tab were assembled in this order. The low-temperature electrolyte prepared in Example 1 was directly dripped onto the Whatman diaphragm and allowed to stand for 12 hours to obtain a sodium ion battery.
[0088] Comparative application example 1
[0089] Conventional lithium cobalt oxide battery.
[0090] Comparative Application Example 2
[0091] Conventional lithium manganese phosphate battery.
[0092] Comparative Application Example 3
[0093] Conventional ternary battery.
[0094] The batteries of comparative application examples 1 to 3 are the batteries described in paragraph
[0081] of patent publication number CN107204466A.
[0095] Performance Testing
[0096] (1) Optical photographs of the low-temperature electrolyte prepared in Example 1 and the electrolytes prepared in Comparative Examples 1 to 6 at different temperatures are shown in FIG. Figure 1 shown.
[0097] from Figure 1 It can be seen that the low-temperature electrolyte prepared in Example 1 was not frozen at -50°C, while electrolytes of other concentrations were all frozen.
[0098] (2) The Raman spectra of the low-temperature electrolyte prepared in Example 1, the electrolyte prepared in Comparative Examples 1 and 4, and deionized water are compared as follows: Figure 2 shown.
[0099] from Figure 2 It can be seen that: at 2850~3750cm -1 The OH stretching vibration bands appearing in the range are caused by the hydrogen bonding network between free water molecules. -1 The shoulder peak intensity at 77° is significantly weakened, and the peak position gradually moves to a higher wave number. This indicates that the content of strong hydrogen bond water (SHW) is decreasing, and the hydrogen bond structure network is gradually destroyed, resulting in a decrease in the freezing point of the solution. The SHW content in the low-temperature electrolyte prepared in Example 1 is the lowest, indicating that the freezing point of the mixed electrolyte at this concentration is the largest.
[0100] (3) The sodium ion battery prepared in Example 1 is as follows Figure 3 As shown, the low temperature cycle performance test was carried out at a current density of 10C, and the results are as follows Figure 4 shown.
[0101] from Figure 4 It can be seen that the sodium ion battery assembled in Application Example 1 is heated at -40°C at 10C (1C = 150 mA g -1 ) After 10,000 repeated charge and discharge cycles, there was no obvious capacity decay and the coulombic efficiency was about 99%, indicating that the electrolyte has excellent cycle performance.
[0102] (4) The conductivity comparison results of the low-temperature electrolyte prepared in Example 1 and the aqueous sodium ion battery electrolyte prepared in Comparative Example 7 are as follows: Figure 5 As shown, (a) is an aqueous sodium ion battery electrolyte, and (b) is the low-temperature electrolyte prepared in Example 1.
[0103] from Figure 5 It can be seen that the aqueous sodium ion battery electrolyte (1 mol / L Na2SO4) of Comparative Example 7 has no conductivity in the temperature range of -5 to -50°C due to complete solidification; the low-temperature electrolyte prepared in Example 1 still has a high ionic conductivity (9.36 mS·cm -1 ).
[0104] (5) The capacity retention rate test comparison results of the sodium ion battery prepared in Application Example 1 and other batteries are shown in Table 1.
[0105] Table 1 Capacity retention rate of sodium ion batteries and other batteries prepared in Application Example 1
[0106]
[0107] As shown in Table 1, the capacity retention rates of the batteries of Comparative Application Examples 1 to 3 at -20°C are 60%, 60%, and 70%, respectively, and the capacity retention rate of the sodium ion battery prepared in Application Example 1 at -20°C is 78.2%, which has certain advantages; at -40°C, the batteries of Comparative Application Examples 1 to 3 all completely fail and cannot work normally, while the sodium ion battery prepared in Application Example 1 can still work normally and has a capacity retention rate of 63.8%.
[0108] (6) Comparison of the actual application scenarios of the sodium ion battery prepared in Application Example 1 and the commercial battery (LR44 button battery produced by Shenzhen Beidongli Technology Co., Ltd.) Figure 6 shown.
[0109] like Figure 6 As shown, the commercial battery is completely unable to work at -40°C; while the sodium ion battery prepared in Application Example 1 can still light up the LED bulb at -40°C.
[0110] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A low-temperature electrolyte, characterized in that: It comprises magnesium salt, sodium salt and water; the molar ratio of the magnesium salt to the sodium salt is (2.5-3.0):0.
5.
2. The low-temperature electrolyte according to claim 1, characterized in that The magnesium salt includes one or more of magnesium chloride, magnesium perchlorate and magnesium nitrate; the magnesium chloride is anhydrous magnesium chloride and / or magnesium chloride hexahydrate.
3. The low-temperature electrolyte according to claim 1, characterized in that The sodium salt includes one or more of sodium chloride, sodium hexafluorophosphate, sodium nitrate, sodium perchlorate and sodium trifluoromethanesulfonate.
4. The low-temperature electrolyte according to claim 1, characterized in that The ratio of the amount of the magnesium salt to the volume of water is (2.5-3.0) mol:1L.
5. The method for preparing the low-temperature electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are involved: The magnesium salt, the sodium salt and water are mixed to obtain the low-temperature electrolyte.
6. The preparation method according to claim 5, characterized in that: The mixing is carried out under stirring conditions, and the stirring speed is 300-400 r / min.
7. Use of the low-temperature electrolyte according to any one of claims 1 to 4 or the low-temperature electrolyte prepared by the preparation method according to claim 5 or 6 in a sodium ion battery.
8. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The electrolyte is the low-temperature electrolyte described in any one of claims 1 to 4 or the low-temperature electrolyte prepared by the preparation method described in claim 5 or 6.
9. The sodium ion battery according to claim 8, characterized in that: The method for preparing the positive electrode sheet comprises the following steps: Na2CoFe(CN)6, a conductive agent and a binder are mixed and ground, and the obtained mixture is mixed with an organic solvent to obtain a positive electrode slurry; The positive electrode slurry is coated on a substrate and then dried to obtain the positive electrode sheet.
10. The sodium ion battery according to claim 8, characterized in that: The method for preparing the negative electrode sheet comprises the following steps: The activated carbon, the conductive agent and the binder are mixed and ground, and the obtained mixture is mixed with an organic solvent to obtain a negative electrode slurry; The negative electrode slurry is coated on a substrate and then dried to obtain the negative electrode sheet.
Citation Information
Cited By
Negative electrode electrolyte of total-iron flow battery as well as preparation method and application of negative electrode electrolyte
CN120109252A
